2020
DOI: 10.1101/2020.11.30.405688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

To the canopy and beyond: Air samples reveal wind dispersal as a driver of ubiquitous protistan pathogen assembly in tree canopies

Abstract: We analyzed air dispersal of the protistan phyla Cercozoa and Oomycota with an air sampler near the ground (~2 m) and in tree crowns (~25 m) of three tree species (oak, linden and ash) in a temperate floodplain forest in March (before leafing) and May (after leaf unfolding) with a cultivation-independent high throughput metabarcoding approach. Both, Cercozoa and Oomycota, contain important pathogens of forest trees and other vegetation. We found a high diversity of Cercozoa and Oomycota in air samples with 122… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…Oomycete community compositions were in fact slightly, yet significantly distinct for every sampling and correspondingly for every season (Table 1). This pattern is in line with hypotheses proposed by Jauss et al (2020a), that seasonal variation in air samples drives the community composition in forest ecosystems. The environment, however, then selects the species most adapted to the microhabitat, leading to overall similar community patterns and microhabitat differences for every season ( Figure 5).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Oomycete community compositions were in fact slightly, yet significantly distinct for every sampling and correspondingly for every season (Table 1). This pattern is in line with hypotheses proposed by Jauss et al (2020a), that seasonal variation in air samples drives the community composition in forest ecosystems. The environment, however, then selects the species most adapted to the microhabitat, leading to overall similar community patterns and microhabitat differences for every season ( Figure 5).…”
Section: Discussionsupporting
confidence: 92%
“…Comparing the data from Spring 2019 ( Figure 1D,H) with air samples previously published by Jauss et al (2020a) (Figure 2) revealed that the air surrounding canopy and ground habitats was dominated by obligate biotrophic OTUs, irrespective of incidence or abundance.…”
Section: Taxonomic and Functional Annotationmentioning
confidence: 68%
See 3 more Smart Citations